Desain Kawasan Agrowisata Persawahan Di Desa Konga, Kecamatan Titehena, Kabupaten Flores Timur - Mochdar, Dian Fitriawati (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2022)
ABSTRACT Agrotourism is a form of tourism activity that utilizes the potential of agricultural business both agricultural technology and agricultural commodities in which there is land preparation, maintenance, harvesting, processing of crops until it is ready to be marketed with the aim to expand knowledge, recreational experience and business relations in agriculture and can increase the added value of agricultural activities and the welfare of surrounding communities. Planning a Rice Field Agrotourism Area in Konga Village with Landscape Concept as a design reference oriented to the general public or tourists as users is needed to accommodate recreational activities in the area. The method used is an architectural design method with the concept of Landscape Architecture as a design reference. The analysis used in this design includes the analysis of the site, the actor, the amount of space, the shape, the structure, the material, the outdoor space and the utility. The results obtained from the Rice Field Agrotourism Area Design in Konga Village are presenting tourism related to the world of agriculture in rice fields with the concept of landscape architecture themes. Applications in the design are the processing of the site, namely differences in the elevation of the building, the application of wood materials on the walls of buildings and circulation bridges in rice fields, the use of paving blocks in human and vehicle circulation and parking areas, garden arrangements for green areas of water catchment, shade vegetation, steering. Keywords:Agrotourism, Landscape, Konga